Study of the Aqueous and Alcoholic Extracts of Sage Leaves (Salvia officinalis) on the growth of pathogenic bacteria in Sirte City - Wafiyah M. Amhalhil; Zenb M.Abd Alrahmn (Surman Journal of Science and Technology, 2025)
This study assesses the antimicrobial properties of natural products derived from sage leaves (Salvia officinalis), a member of the Lamiaceae family, against five pathogenic bacterial strains. The investigation employs aqueous and alcoholic sage leaf extracts, prepared using both cold and hot water. The bacterial strains included in the study were Staphylococcus, Streptococcus pyogenes, Escherichia coli, Salmonella, and Shigella. The chemical examination also revealed the presence of significant active components in these extracts, including tannins, saponins, flavonoids, glycosides, resins, and alkaloids. The inhibition results of the extracts exhibited variability contingent on the extraction method, temperature, and solvent employed, thereby reinforcing the assertion that this plant merits consideration as a prospective natural antibiotic. It is therefore recommended that further quantitative and qualitative studies be conducted in order to determine the molecular structure of the active components present and to reduce reliance on synthetic compounds that may have harmful effects on humans.